“Aplicación de clarificantes en la elaboración de vino de mora (Rubus ulmifolius) y fresa (Fragaria vulgaria) en el emprendimiento Cacique Tisaleo. - Zumba Maliza, Ana Lucía (2023)
Clarification is an oenological technique used since ancient times to remove suspended particles from wine. The main objective on this research was to evaluate four fining agents (potato protein extract, moringa, activated charcoal and bentonite) into two concentrations (1.5% and 3%) to determine which of the fining agents works best within the clarification process of blackberry (Rubus ulmifolius) and strawberry (Fragaria vulgaria) wine, resulting in the turbidity reduction. The physicochemical properties (pH, total acidity, soluble solids, alcohol content and turbidity) and microbiological properties (total aerobes, molds and yeasts) were carried out in triplicate using the method described in NTE INEN 374. For the sensory part, were selected the three best treatments (Mor 3%, Ben 1.5% and Ben 3%) that were compared with the reference sample. The statistical design applied was the A*B+1 factorial design. On this way, was determined that the physicochemical properties of the wine showed significant differences (p<0.05) for the fining agents and concentrations. The best results were achieved when using moringa 3%, it showed 3.32 pH; 3.64 g/l tartaric acid; 5.47 ° brix; 10.4 % alcohol. Turbidity decreased by 70% from 1040 NTU to 310 NTU, which shows that it is possible to use moringa in the clarification of fruit wines.